Cross-sectional survey comparing HIV risk behaviours of adolescent and young adult men who have sex with men only and men who have sex with men and women in the US and Puerto Rico. (13th January 2015) - Ellen, Jonathan M; Greenberg, Lauren; Willard, Nancy; Stines, Stephanie; Korelitz, James; Boyer, Cherrie B
Abstract : Objective: To examine the HIV risk behaviours of men who have sex with men only (MSMO) and men who have sex with men and women (MSMW), aged 12–24 years, in five US cities and in San Juan, Puerto Rico. Methods: Data were collected through four annual cross-sectional anonymous surveys at community venues and included questions about sexual partnerships, sexual practices including condom use and substance use. Demographic and risk profiles were summarised for both groups. Results: A total of 1198 men were included in this analysis, including 565 MSMO and 633 MSMW. There were statistically significant differences between the two groups for many risk factors examined in multivariable models. MSMW were more likely to identify as bisexual, be in a long-term relationship, have a history of homelessness, have ever used marijuana, have ever been tested for HIV and to have been tested for HIV within the past 6 months. MSMW may be more likely to ever exchange sex for money and ever have a sexually transmitted infection than MSMO. Conclusions: MSMW were more likely to report several markers of socioeconomic vulnerability or behaviours associated with increased risk for HIV than MSMO. MSMW contribute to HIV prevalence in the USA, and better understanding of the risk profile of this group is essential to understand heterosexual HIV transmission. MSMW, particularly those who identify as bisexual or questioning, may feel uncomfortable participating in programmes that are designed for gay-identified men. Therefore, prevention strategies need to target distinct subgroups that compose the population of MSM.